Backpacking with children : how to go lightweight, have fun, and stay safe on the trail / Malia Maunakea. - Maunakea, Malia (Colorado Mountain Club Press, 2023)
"Backpacking together can be an unforgettable adventure that your family will treasure for years to come. But a successful family outing takes planning. Knowing how to prepare, where to go, and what to bring are crucial. In Backpacking with Children, author and seasoned hiking mom Malia Maunakea teaches the basics of backpacking with kids--how to make it easy, fun, and as lightweight as possible without breaking the bank."--Back cover.